Corporate Governance Mechanism and Corporate Performance: A Literature Review - Ifta Almazah Suhaya; Bernardus Yuliarto Nugroho (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper aims to describe the importance of corporate governance and company performance in a company. This research method uses qualitative research methods with a literature review approach. Sources of research data are journal articles from research results between corporate governance and corporate performance. The results of the country study show that each has its own corporate governance model. Corporate governance models such as the one-level system and the two-level system can influence the corporate governance mechanism, as well as being able to control the company's performance.